2005
DOI: 10.1111/j.1399-6576.2005.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adding intrathecal magnesium sulphate to bupivacaine–fentanyl spinal anaesthesia

Abstract: In patients undergoing lower extremity surgery, the addition of IT magnesium sulphate (50 mg) to spinal anaesthesia induced by bupivacaine and fentanyl significantly delayed the onset of both sensory and motor blockade, but also prolonged the period of anaesthesia without additional side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
90
2
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 23 publications
(26 reference statements)
12
90
2
4
Order By: Relevance
“…Similar findings were observed in other studies. 17,[21][22][23] Among these studies, two studies 17,23 compared magnesium sulphate as adjuvant to intrathecal bupivacaine where as in the other two studies 21,22 intrathecal fentanyl was also added and concluded the same. The duration of motor block was same in both the groups in another study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were observed in other studies. 17,[21][22][23] Among these studies, two studies 17,23 compared magnesium sulphate as adjuvant to intrathecal bupivacaine where as in the other two studies 21,22 intrathecal fentanyl was also added and concluded the same. The duration of motor block was same in both the groups in another study.…”
Section: Discussionmentioning
confidence: 99%
“…(4)(5)(6) Trials with intrathecal and epidural magnesium administration have shown that magnesium is a valuable adjuvant analgesic, but very few data are available on its analgesic effects in lung resection surgery. (7)(8)(9)(10) The aim of the present study was to assess effects of continuous epidural magnesium infusion during thoracic surgery on intraoperative sufentanil consumption and postoperative analgesic requirements during first 48 hours after surgery.…”
mentioning
confidence: 99%
“…Magnezyum pür analjezik etkili olmamakla birlikte, N-metil-D-aspartat (NMDA) reseptör antagonisti olarak medulla spinaliste ağrının işlenmesi ve modülasyonunda rol oynamaktadır. Bu etkileri ile intratekal uygulanan MgSO 4 'ın opiyoidlerin analjezik etkisini değiştire-bildiği kliniğimizde yapılan bir çalışma ile daha önce gösteril-miştir (4). Ayrıca ratlarda iv olarak uygulanan magnezyumun karaciğer mikrozomal enzim indüksiyonu yaparak amid yapıdaki lokal anestetiklerin etkisini kısalttığı da gösterilmiştir (5).…”
unclassified
“…Ayrıca ratlarda iv olarak uygulanan magnezyumun karaciğer mikrozomal enzim indüksiyonu yaparak amid yapıdaki lokal anestetiklerin etkisini kısalttığı da gösterilmiştir (5). Ancak preeklamptik gebelerde spinal anestezi sırasın-da uygulanan bupivakainin etkinliği üzerine iv uygulanan MgSO 4 'ın etkisi ile ilgili çalışma mevcut değildir.…”
unclassified
See 1 more Smart Citation